Metal lithium negative electrode surface modification method and application of metal lithium negative electrode surface modification method in lithium battery
By using a modified solution containing SnCl4 in a lithium battery to treat the metal lithium negative electrode, Li-Sn alloy and LiCl modified layer are generated, the problems of lithium dendrites formation and irreversible consumption are solved, and the cycle stability and first-time efficiency of the battery are improved.
Patent Information
- Application Number
- CN202310985829.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-14
AI Technical Summary
In existing lithium batteries, lithium dendrites are easily formed on the surface of metal lithium, resulting in safety hazards and irreversible consumption, reducing the reversibility and cycle life of the battery.
The metal lithium negative electrode was treated with a modified solution containing SnCl4 to form a modified layer with Li-Sn alloy and LiCl, which inhibited the formation of lithium dendrites and protected metal lithium.
It improves the cycle stability and first-time efficiency of metal lithium batteries, extends the cycle life of the battery, and avoids the formation of lithium dendrites.
Smart Images

Figure CN119447194A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a method for modifying the surface of a metallic lithium negative electrode and its application in lithium batteries. Background Art
[0002] Secondary lithium (Li) metal batteries (LMBs) are expected to achieve greater than 300 Wh kg -1 The energy density of lithium ions has always been a focus of attention. However, Li dendrites are easily formed on the surface of lithium metal, which can easily cause serious safety hazards; at the same time, the active reduction ability makes Li and the electrolyte in the battery very easy to react, resulting in irreversible consumption of the two, thereby reducing the reversibility and cycle life of the battery. Although electrochemical reduction strategies have been proposed to solve these problems, the lithium metal formed by electrochemical reduction will still be deposited at the electrode / electrolyte interface, producing a new lithium metal surface, which will further react with the electrolyte and still pose a risk of dendrite formation. Therefore, metal lithium batteries need to use excess electrolyte and lithium metal to compensate for the irreversible consumption of the two and extend the battery cycle life, but at the expense of the battery's energy density.
[0003] Therefore, it is necessary to develop an economical and simple lithium electrode processing method to solve the above problems. Summary of the invention
[0004] The present application provides a method for modifying the surface of a metallic lithium negative electrode and its application in a lithium battery, so as to solve the technical problems that the existing lithium electrode is prone to generate lithium dendrites and the lithium electrode and electrolyte are irreversibly consumed due to the reaction. In a first aspect, the present application provides a method for surface modification of a metallic lithium negative electrode, the method comprising the following steps: After the metal lithium sheet is immersed in the modification solution for 2-12 hours, a modification layer is formed on the surface, and then the sheet is taken out and dried to obtain a modified metal lithium negative electrode; The modified solution includes 1%-10% of tin chloride, and the volume ratio of the metal lithium sheet to the modified solution is 0.1:100-20:100.
[0005] Optionally, the thickness of the metal lithium sheet is 3 μm to 2 mm.
[0006] Optionally, the thickness of the modification layer is 2-10 μm.
[0007] Optionally, the modified solution comprises an organic solvent, and the organic solvent is selected from at least one of THF, DMSO, toluene, benzene, xylene, and ethyl acetate.
[0008] Optionally, the drying is performed by vacuum drying, the drying temperature is 80 to 178°C, and the drying time is 30 min to 24 h.
[0009] In a second aspect, the present invention provides a lithium battery, comprising a modified metal lithium negative electrode prepared by the surface modification method of the metal lithium negative electrode described in the first aspect.
[0010] Optionally, the lithium battery also includes a positive electrode nickel material and an electrolyte.
[0011] Optionally, the positive electrode nickel material includes any one of NCM523, NCM622, NCM811, Ni90 and NCA.
[0012] The above technical solution provided by the present invention has the following advantages compared with the prior art: The present invention provides a method for modifying a metal lithium negative electrode and application thereof in a lithium battery. The method adopts a solution containing SnCl4 to treat a metal lithium negative electrode, utilizes SnCl4 to react with metal lithium, generates a modified layer having a Li-Sn alloy and LiCl and deposits it on the surface of the lithium negative electrode, wherein the generated LiCl can effectively protect the side reaction of the metal lithium with an electrolyte, and on the other hand, the generated Li-Sn alloy can further induce the deposition of metal lithium and inhibit the formation of lithium dendrites, thereby improving the cycle stability of the metal lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0014] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0015] Figure 1 A schematic diagram of a process for modifying a metallic lithium negative electrode provided in an embodiment of the present application; DETAILED DESCRIPTION In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0016] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0017] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items (individuals) or plural items (individuals). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or plural, respectively.
[0018] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0019] Studies have found that negative electrode materials (Si, Sn, etc.) based on electrochemical alloying reactions allow Li ions to diffuse into the interior of the electrode material to form an alloy phase, which can avoid the formation of dendrites and form a more stable electrode / electrolyte interface. The electrochemical alloying reactions of Li can be divided into two categories: (1) reconstruction reactions and (2) solid solution reactions. Reconstruction reactions represented by Si and Sn involve significant changes in the crystal structure and high reaction activation energy. Therefore, the discharge-charge voltage hysteresis is large, and the oxidation / reduction potential is much higher than the Li / Li+ potential. In contrast, the structural changes in the solid solution reaction during the lithiation-delithiation process are much smaller, so it can be carried out at extremely close to the Li / Li+ potential. + When this solid solution reaction dominates the lithiation-delithiation process, the newly generated Li atoms on the surface of the metal foil can penetrate into the metal to form an alloy phase instead of being deposited on the metal surface to form metallic lithium, thus avoiding the formation of lithium dendrites and inhibiting side reactions.
[0020] Therefore, the present invention provides a method for modifying a metallic lithium negative electrode, see Figure 1 , the method comprising: After the metal lithium sheet is immersed in the modification solution for 2-12 hours, a modification layer is formed on the surface, and then the sheet is taken out and dried to obtain a modified metal lithium negative electrode; The modified solution includes 1%-10% of tin chloride, and the volume ratio of the metal lithium sheet to the modified solution is 0.1:100 to 20:100.
[0021] In some embodiments, the thickness of the metal lithium sheet is 3 μm to 2 mm, and the thickness of the modified layer formed on the surface is 2 to 10 μm.
[0022] In some embodiments, the modified solution uses an organic solvent, and the organic solvent is selected from at least one of THF, DMSO, toluene, benzene, xylene, and ethyl acetate.
[0023] In some embodiments, when the metal lithium sheet is dried after immersion, a vacuum dryer is used for drying, and the drying temperature is 80 to 178° C. and the drying time is 30 min to 24 h.
[0024] In a preferred embodiment, the drying temperature is 120° C. and the drying time is 24 hours.
[0025] In a second aspect, the present invention provides a lithium battery, comprising a modified metal lithium negative electrode prepared by the metal lithium negative electrode surface modification method described in the first aspect, and also comprising a positive electrode nickel material, a separator and an electrolyte.
[0026] In some embodiments, the positive electrode nickel material includes any one of NCM523, NCM622, NCM811, Ni90 and NCA.
[0027] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0028] Example 1 Step 1: Prepare the modified solution: dissolve 1 part of SnCl4 in 50 parts of THF and 50 parts of DMSO mixed solution to prepare SnCl4 / THF, DMSO mixed solution, and stir for 30 minutes.
[0029] Step 2: Soak the lithium metal sheet in the above solution for 12 hours.
[0030] Step 3: Take out the soaked lithium sheet and dry it in an oven at 120°C in an argon atmosphere for 24 hours to obtain a modified metal lithium sheet.
[0031] Step 4: Take out the modified lithium metal sheet and assemble it into a button lithium battery with the positive electrode nickel material NCM811, a separator and a small amount of electrolyte.
[0032] Example 2 Step 1: Dissolve 2.5 parts of SnCl4 in a mixed solution of 50 parts of THF and 50 parts of DMSO to prepare a mixed solution of SnCl4 / THF and DMSO, and stir for 30 minutes.
[0033] Step 2: Soak the lithium metal sheet in the above solution for 5 hours.
[0034] Step 3: Take out the soaked lithium sheet and dry it in an oven at 120°C in an argon atmosphere for 24 hours to obtain a modified metal lithium negative electrode.
[0035] Step 4: Take out the modified lithium metal and assemble it into a button battery with NCM811, diaphragm and a small amount of electrolyte.
[0036] Example 3 Step 1: Dissolve 5 parts of SnCl4 in 50 parts of THF and 50 parts of DMSO mixed solution to prepare SnCl4 / THF, DMSO modified solution and stir for 30 minutes.
[0037] Step 2: Soak the lithium metal sheet in the above solution for 4 hours.
[0038] Step 3: Take out the soaked lithium sheet and dry it in an oven at 120°C in an argon atmosphere for 24 hours to obtain a modified metal lithium negative electrode.
[0039] Step 4: Take out the modified lithium metal and assemble it into a button battery with NCM811, a separator and a small amount of electrolyte.
[0040] Example 4 Step 1: Dissolve 7.5 parts of SnCl4 in 50 parts of THF and 50 parts of DMSO mixed solution to prepare SnCl4 / THF, DMSO modified solution, and stir for 30 minutes.
[0041] Step 2: Soak the lithium metal sheet in the above solution for 3 hours.
[0042] Step 3: Take out the soaked lithium sheet and dry it in an oven at 120°C in an argon atmosphere for 12 hours to obtain a modified metal lithium negative electrode.
[0043] Step 4: Take out the modified lithium metal negative electrode and assemble it into a button battery with NCM811, separator and a small amount of electrolyte.
[0044] Comparative Example 1 The surface density of the mass-produced electrode is 20 mg / cm 2 The NCM9 series, 600μm lithium sheet as the negative electrode, with the separator and a small amount of electrolyte assembled into a button battery.
[0045] The button cells obtained in the above four embodiments and one comparative example were subjected to the same experimental test, and the results are shown in Table 1 below: Table 1 It can be seen from the above table that the button metal lithium battery prepared in Comparative Example 1 has a 0.1C charging capacity of 235.4 mAh / g, a discharge capacity of 214.3 mAh / g, an initial efficiency of 90.87%, and a capacity decay to 80.88% after only 22 cycles.
[0046] The button cell prepared in Example 1 has a 0.1C charging capacity of 236.1 mAh / g, a discharge capacity of 215.0 mAh / g, and an initial efficiency of 91.11%. After 80 cycles, the capacity decays to 93.92%. It can be seen that the button cell significantly improves its cycle performance, and also has certain improvements in the initial efficiency and specific capacity. This is because the metal lithium negative electrode is treated with a solution (1%) containing SnCl4, and SnCl4 is used to react with metal lithium to generate Li-Sn alloy and LiCl. LiCl is similar to LiF, and LiF is one of the main components of the SEI film, which can effectively protect the side reaction of metal lithium with the electrolyte. Therefore, the LiCl generated in the present invention can also effectively protect the side reaction of metal lithium with the electrolyte; on the other hand, the generation of Li-Sn alloy can further induce metal lithium deposition and inhibit the formation of lithium dendrites, thereby improving the cycle stability of the metal lithium battery. In addition, since the battery in Example 1 is provided with the above-mentioned modified layer, it can prevent the further reaction of metal lithium with the electrolyte, so its initial efficiency can be improved.
[0047] The button cell prepared by Example 2 has a 0.1 C charging capacity of 237.1 mAh / g, a discharge capacity of 216.3 mAh / g, an initial efficiency of 91.21%, and a capacity decay of only 94.31% after 80 cycles. The difference between Example 2 and Example 1 is that the button cell in Example 2 uses a 2.5% SnCl4 solution to treat the metal lithium negative electrode, while Example 1 only uses a 1% SnCl4 solution for treatment. Compared with Example 1, the Li-Sn alloy and protective layer formed by the metal lithium negative electrode in Example 2 are thicker, so it has better initial efficiency and cycle capacity to a certain extent. However, with the increase of SnCl4 concentration (such as the experimental data in Example 3 and Example 4), the thickness of the protective layer of Li-Sn alloy and LiCl formed is thicker, but it also affects its electronic conductivity to a certain extent. At the same time, there is a certain irreversible phase reaction of Li-Sn on the surface, which will consume a certain amount of lithium ions from the positive electrode, resulting in a decrease in its initial efficiency and a decay of the cycle performance. Therefore, the experimental data of the button battery data provided in Example 3 and Example 4 are relatively poor, but the cycle data are also higher than the data in the comparative example.
[0048] In summary, the treatment of the metal lithium negative electrode with a tin chloride concentration of 1%-10% provided in the present application helps to inhibit lithium dendrites on the surface of the metal lithium negative electrode and improve the cycle stability performance of the metal lithium battery.
[0049] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for modifying the surface of a metallic lithium negative electrode, characterized in that: The method comprises: After the metal lithium sheet is immersed in the modification solution for 2-12 hours, a modification layer is formed on the surface, and then the sheet is taken out and dried to obtain a modified metal lithium negative electrode; The modified solution includes 1%-10% of tin chloride, and the volume ratio of the metal lithium sheet to the modified solution is 0.1:100-20:
100.
2. The method for modifying the surface of a metallic lithium negative electrode according to claim 1, characterized in that: The thickness of the metal lithium sheet is 3 μm to 2 mm.
3. The method for surface modification of a metallic lithium negative electrode according to claim 1, characterized in that: The thickness of the modified layer is 2-10 μm.
4. The method for modifying the surface of a metallic lithium negative electrode according to claim 1, characterized in that: The modified solution comprises an organic solvent, and the organic solvent is selected from at least one of THF, DMSO, toluene, benzene, xylene, and ethyl acetate.
5. The method for surface modification of a metallic lithium negative electrode according to claim 1, characterized in that: The drying is carried out by vacuum drying, the drying temperature is 80 to 178°C, and the drying time is 30 min to 24 h.
6. A lithium battery, characterized in that: It comprises a modified metal lithium negative electrode prepared by the metal lithium negative electrode surface modification method described in any one of claims 1-5.
Citation Information
Patent Citations
Method for polishing lithium metal and application thereof
CN111463405A
Preparation method of lithium metal negative electrode and lithium metal negative electrode
CN113299886A
Manufacturing method of lithium anode containing protection layer, lithium anode manufactured thereby and lithium secondary battery applied thereby
KR1020180053481A
Electrochemical device
WO2023136612A1